Molecular Analysis of H5N1 Avian Influenza Virus from Avian Species: Compared with Genbank Data of the Indonesian H5N1 Human Cases - NI LUH PUTU INDI DHARMAYANTI (Microbiology Indonesia, 2009)
In Indonesia, the H5N1 avian influenza (AI) disease has been circulating for more than five years and has infected various types of avian species and human beings. Generally, avian influenza cases in human beings are suspected to be spread by chicken, birds or waterfowl previously infected by avian influenza. The data supporting this assumption were very limited, therefore the molecular characterization on four avian influenza genome segments such as hemagglutinin, neuraminidase, matrix and non structural that was isolated from the avian species surrounding the avian influenza cases in human was conducted. The analysis was conducted on these genes which were responsible for binding receptors, the pathogenicities, and the resistance to antiviral drugs, thus the virus changes can be detected by comparing the sequence data of GenBank from human cases related to the avian species. The four avian influenza viruses used in this study isolated from avian influenza cases surrounding the avian influenza cases in human in 2007. The results of genetic analysis showed that these four viruses and the available sequence data from the GenBank for of avian influenza virus in human and avian have the receptor a-2,3 of sialic acid which is the avian receptor. The A/Ck/West Java/Bks2/2007 virus is collected from the chicken surrounding the avian influenza cases in human that resembles the data of avian influenza virus from human, A/Indonesia/CDC1031/2007 from GenBank. The viruses conferred similarities amino acid sequence of hemagglutinin, neuraminidase, matrix and non structural protein. All viruses used have deletion at the position 80-84 of the NS1 protein and possessed the ESEV motif which may contribute to an increased virulence. The avian influenzaviruses examined in this study also show resistance to amantadine